1982
DOI: 10.1097/00000658-198207000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Biliary Calculi Duodenal Diverticula as a Predisposing Factor

Abstract: Several studies indicate a causal relationship between duodenal diverticula and gallstone disease. The diverticula persist after biliary tract surgery, and it is therefore presumed that patients with diverticula have an increased disposition to develop new calculi in the bile ducts after cholecystectomy. To test this hypothesis, the occurrence of recurrent biliary calculi was studied in 101 patients who had cholecystectomy, all with an asymptomatic period of two years or more following the primary biliary surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The variation is due to the different study methods used and the different ages of the subjects investigated. A recent barium study showed a prevalence of 6% [1], and in studies employing endoscopic retrograde cholangiopancreatography (ERCP), it varied between 4.1 and 31.7%, with most around 10–20% [2,3,4,5,6,7,8,9]. On the other hand, a rate of 19.4% has been reported at autopsy [10].…”
Section: Incidence Of Jpdmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation is due to the different study methods used and the different ages of the subjects investigated. A recent barium study showed a prevalence of 6% [1], and in studies employing endoscopic retrograde cholangiopancreatography (ERCP), it varied between 4.1 and 31.7%, with most around 10–20% [2,3,4,5,6,7,8,9]. On the other hand, a rate of 19.4% has been reported at autopsy [10].…”
Section: Incidence Of Jpdmentioning
confidence: 99%
“…In this study, biliary calculi indicated choledocholithiasis and cholecystolithiasis, collectively. When these two sites where stones exist are studied separately, most papers have accepted the fact that choledocholithiasis was primarily correlated with JPD [3,4,5,6] (fig. 2).…”
Section: Jpd and Biliary Tract Diseasementioning
confidence: 99%
“…The incidence of JPD increases with age23; this may induce bacterial contamination of bile in patients with an incompetent sphincter resulting in primary CBD stone formation 24. A JPD was present in 60% of our patients, probably due to their age (median age 66 years), but it was not a significant factor for recurrent CBD stones or delayed biliary emptying in this study.…”
Section: Discussionmentioning
confidence: 50%
“…However, numerous factors associated with their origin appear to be of importance. With regard to the formation of concretions in the biliary duct, there are adequate findings concerning the effects of benign or malignant strictures, of bacterial infection and parasites, and of metabolic changes and dietary habits, as well as those of anatomical conditions in the bilioduodenal region [1][2][3][4][5][6]. However, there are only sporadic reports about for eign material as a cause of lithiasis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%